Desorption kinetics evaluation for the development of validated desorption electrospray ionization-mass spectrometric assays for drug quantification in tissue sections - Fresnais, Margaux; Liang, Siwen; Seven, Deniz; Prodanovic, Nevena; Sundheimer, Julia; Haefeli, Walter E.; Burhenne, Jürgen; Longuespée, Rémi (International journal of molecular sciences, 2023)
The development of desorption/ionization (DI) mass spectrometric (MS) assays for drug quantification in tissue sections and their validation according to regulatory guidelines would enable their universalization for applications in (clinical) pharmacology. Recently, new enhancements in desorption electrospray ionization (DESI) have highlighted the reliability of this ion source for the development of targeted quantification methods that meet requirements for method validation. However, it is necessary to consider subtle parameters leading to the success of such method developments, such as the morphology of desorption spots, the analytical time, and sample surface, to cite but a few. Here, we provide additional experimental data highlighting an additional important parameter, based on the unique advantage of DESI-MS on continuous extraction during analysis. ...